Identifying Patterns of Situational Clustering and Contextual Variability in Criminological Data: An Overview of Conjunctive Analysis of Case Configurations: - Hart, Timothy C. (Journal of contemporary criminal justice, 2017)
Conjunctive analysis of case configurations (CACC) is a recent innovative approach developed by Miethe, Hart, and Regoeczi that bridges the gap between traditional quantitative- or qualitative-based studies approaches. CACC was initially designed for large sample application of exploratory and confirmative studies in criminology and criminal justice. However, as this special issue demonstrates, its application has since broadened. In this introductory article, we provide background material of conjunctive analysis by (a) presenting information on how to conduct a CACC study and (b) describing the conceptual and methodological framework surrounding this type of case comparative method. With this foundation, readers can better appreciate the distinct and unique contributions of the five pieces of CACC research making up this special issue.